Structure-activity relationship of 2-oxoamide inhibition of group IVA cytosolic phospholipase A2 and group V secreted phospholipase A2 - Six, D. A.; Barbayianni, E.; Loukas, V.; Constantinou-Kokotou, V.; Hadjipavlou-Litina, D.; Stephens, D.; Wong, A. C.; Magrioti, V.; Moutevelis-Minakakis, P.; Baker, S. F.; Dennis, E. A.; Kokotos, G. (Journal of Medicinal Chemistry, 2007)
The Group IVA cytosolic phospholipase A2 (GIVA cPLA2) is a key provider of substrates for the production of eicosanoids and platelet-activating factor. We explored the structure−activity relationship of 2-oxoamide-based compounds and GIVA cPLA2 inhibition. The most potent inhibitors are derived from δ- and γ-amino acid-based 2-oxoamides. The optimal side-chain moiety is a short nonpolar aliphatic chain. All of the newly developed 2-oxoamides as well as those previously described have now been tested with the human Group V secreted PLA2 (GV sPLA2) and the human Group VIA calcium-independent PLA2 (GVIA iPLA2). Only one 2-oxoamide compound had appreciable inhibition of GV sPLA2, and none of the potent GIVA cPLA2 inhibitors inhibited either GV sPLA2 or GVIA iPLA2. Two of these specific GIVA cPLA2 inhibitors were also found to have potent therapeutic effects in animal models of pain and inflammation at dosages well below the control nonsteroidal anti-inflammatory drugs.
Keywords: amide triacylglycerol analogs; amino-acids; arachidonic-acid; carboxylic-acids; crystal-structure; group iia; lysophospholipase activity; nonsteroidal antiinflammatory drugs; one-pot conversion; selective inhibitor